A multi-scalar view of urban financialization: urban development and local government bonds in China. Issue 8 (3rd August 2022) - Li, Zhenfa; Wu, Fulong; Zhang, Fangzhu
ABSTRACT: How urban financialization is achieved across different government levels receives limited attention. This study addresses the gap by examining the deployment of China's local government bonds (LGBs). LGBs introduce a distinct financialization process in which the government relies on debt-financing for urban development, but in a regulated way to constrain financial risks. Urban financialization is realized through the multi-scalar structure of the government. The centralized procedure strengthens central and provincial regulations on local development projects. The multi-scalar government not only facilitates urban financialization but also executes statecraft by designing the process.